Analysis of The Effectiveness of HSE Committees in Occupational Health and Safety Implementation on Infrastructure Projects - Ponang Pamungkas; Bagus Hario Setiadji; Ferry Hermawan (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The construction industry remains one of the most hazardous sectors due to the complexity of project activities, changing work locations, and the need for consistent safety supervision across diverse operational settings. This study aims to analyse the effectiveness of the Health, Safety, and Environment Committee in supporting occupational health and safety implementation in infrastructure projects managed by Infrastructure 1 Division of PT. X. A qualitative case study approach was employed through in-depth interviews with three project managers, supported by document analysis and field observation. The findings show that the committee played an important role in strengthening safety implementation through leadership support, regular audits, risk assessment, communication, training, and continuous monitoring. The committee also contributed to stronger safety culture, reduced incidents and near misses, and improved regulatory compliance across project sites. The study concludes that the effectiveness of the committee depends on the integration of institutional commitment, operational implementation, and ongoing evaluation. Strengthening committee capacity, cross functional coordination, and digital monitoring is essential to support sustainable safety performance in large scale infrastructure projects.